Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1556-4029.2012.02171.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Observations on the Ability of Hyperspectral Imaging to Provide Detection and Visualization of Bloodstain Patterns on Black Fabrics

Abstract: The analysis of bloodstain patterns can assist investigators in understanding the circumstances surrounding a violent crime. Bloodstains are routinely subjected to pattern analysis, which is inherently dependent upon the ability of the examiner to locate and visualize bloodstain patterns on items of evidence. Often, the ability to properly visualize bloodstain patterns is challenging, especially when the stain patterns occur on dark and/or patterned substrates. In this study, preliminary research was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 8 publications
0
35
0
Order By: Relevance
“…In fact, this combination provides both spatial and spectral information of samples enabling the visualization of stains based on their characteristic spectra. However, most of the studies are exclusively focused on blood detection [18][19][20][21][22][23]. For instance, Morgan et al [18,19] identified diluted blood stains on dark fabrics made of acrylic fibre, cotton, nylon and polyester through the contrast between blood and background when using MIR thermal imaging.…”
Section: Vibrational Spectroscopy In Promising Approaches For Body Flmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, this combination provides both spatial and spectral information of samples enabling the visualization of stains based on their characteristic spectra. However, most of the studies are exclusively focused on blood detection [18][19][20][21][22][23]. For instance, Morgan et al [18,19] identified diluted blood stains on dark fabrics made of acrylic fibre, cotton, nylon and polyester through the contrast between blood and background when using MIR thermal imaging.…”
Section: Vibrational Spectroscopy In Promising Approaches For Body Flmentioning
confidence: 99%
“…In brief, results again proved the superiority of NIR to detect blood stains except for the "small spatter" stains and most of the substances tested were easily distinguished from blood. Schuler et al [22] overcame these results using a wider NIR range (650-1100 nm and 960-1650 nm) and demonstrated the detection and visualization of both transfer/smear and spatter blood stains on black fabrics (cotton and denim). Furthermore, the discrimination among stains of blood and potential false-positive substances such as lotions and lipsticks was achieved based on their different NIR spectral response.…”
Section: Vibrational Spectroscopy In Promising Approaches For Body Flmentioning
confidence: 99%
See 3 more Smart Citations